Ultraviolet light-induced collagen degradation inhibits melanoma invasion - Timothy Budden (Nature Portfolio, 2021)
Ultraviolet radiation (UVR) increases melanoma incidence. Here, the authors report that UVR-damaged dermal fibroblasts upregulate MMP1 to degrade collagen which inhibits melanoma invasion and that aged primary melanomas in skin with degraded collagen have a better prognosis, while new collagen synthesis restores invasion and leads to death.